The evolution of a Weichselian proglacial lake in NW Poland as revealed by static penetration tests - Wierzbicki, Jędrzej; Paluszkiewicz, Renata; Paluszkiewicz, Ryszard (Geologos, 2011)
The lithology, structure and geophysical characteristics of the glaciolacustrine clays deposited in the Wierzchowo pro-glacial lake were determined using static penetration tests (CPTU) in combination with standard lithological measure-ments. The deposits are divided into four lithological units (R1 to R4) on the basis of overconsolidation. Units R3 and R4 are separated by mass-ﬂow deposits. The depositional conditions history of the lake result represent four phases: (1) an initial (low-energy) phase with the deposition of the rhythmically laminated sediments of units R1 and R2, which are divided by an erosional interval; (2) a phase of non-deposition with some desiccation structures and extended consolidation of sediments; (3) the main phase characterised by deposition of the rhythmically laminated sediments of unit R3; and finally, (4) the youngest phase, which represents alternations of deposition and erosion. The results show that sedimentation in the Wierzchowo proglacial lake was less continuous, and that the depositional processes were more complex than in the neighboring Złocieniec glacial lake.